A novel approach to envisage effects of boron in P91 steels through Gleeble weld-HAZ simulation and impression-creep. (November 2022) - Khajuria, Akhil; Akhtar, Modassir; Bedi, Raman
This paper induced a novel methodology for the characterization of creep behavior of weld heat-affected zone (HAZ) for boron-free P91 (PM) and boron modified P91B (B-PM) steels. Gleeble-3800 thermo-mechanical simulator replicated specimens, representing coarse-grain HAZ (CGHAZ), fine-grained HAZ (FGHAZ), and inter-critical HAZ (ICHAZ). Short-term impression creep tests were conducted at 625°C/270-410MPa on PM/B-PM and their simulated HAZs after being subjected to post-weld heat treatment (PWHT) of 760°C/3 h. Microstructural characterization and local strain analyses were accomplished by electron back-scattered diffraction. Simulated microstructures of P91B-FG/ICHAZ after PWHT exhibited lath martensitic structure and large prior-austenite grain size as regards P91-FG/ICHAZ, correspondingly. Average values of local microstructural strain from local average misorientation were relatively high in B-PM and P91B-ICHAZ than PM and P91-ICHAZ, respectively. Similar observations were found for P91-CG/FGHAZ with their counterparts. Stress dependent steady-state creep-rate (SSCR) followed power-law for all specimens except PM. The minimum and maximum ranges of SSCR for P91B specimens were observed to be in a narrower range than P91 specimens. The value of stress exponent for all specimens was evaluated, and corresponding mechanisms were discussed. The analyses of microstructures and corresponding impression creep behavior of P91/P91B samples suggested that modification of 100 ppm boron to P91 steel improved creep-rupture ductility that delayed type IV failure at outer HAZ of P91 steel weldments.